Use of Biochemical Markers in Capoeta trutta (Heckel, 1843) for the Assessment of Aquatic Pollution in Munzur River, Tunceli, Turkey - Yildirim, N.C.; Danabas, D.; Ergin, C. (Asian Journal of Chemistry, 2011)
The potential utility of biomarkers for monitoring both environmental quality and the health of organisms inhabiting polluted ecosystems has received increasing attention during the recent years. In this study, it was aimed to investigate the possible effect of pollution on biochemical parameters of Capoeta trutta captured in two environments with different levels of pollution in Munzur River, Tunceli, Turkey. One of them, hereby named reference site, there is no sewage discharge. Other side is denominated as polluted site is characterized by discharge of domestic sewage. Levels of amylase, alkaline phosphatase, lactate dehydrogenase, high-density lipoprotein cholesterol, cholesterol, albumin, total protein, direct bilirubin, total bilirubin, γ-glutamyl tranferase, aspartate aminotransferase, alanine aminotransferase, urea, creatinine, glucose, triglycerides and uric acid were checked in blood samples. Plasma biochemical changes showed significantly differences between reference and polluted sites in alkaline phosphatase, lactate dehydrogenase, high-density lipoprotein cholesterol, cholesterol, alanine aminotransferase and glucose values. These results indicate that both domestic waste water and agricultural activities can alter the serum biochemical contents of Copeata trutta fish in Munzur River. Continuous production of pollutants resulting in impaired ability to respond to different environment stress factors and diseases. Present groups of researchers suggest that pollution levels should be monitored regularly.